Nematode burdens and cellular responses in the abomasal mucosa and blood of Florida Native, Rambouillet and crossbreed lambs - Amarante, AFT; Craig, T. M.; Ramsey, W. S.; Davis, S. K.; Bazer, F. W. (Elsevier B.V., 1999)
This experiment was carried out to compare the worm burden and cellular responses in the abomasal mucosa and blood of Florida Native and Rambouillet lambs and also in animals produced by crosses of these two breeds (generations F1 and F2). Animals were exposed to infection by gastrointestinal nematodes on three different occasions. The first infection was natural, occurring while they were suckling lambs. After weaning, they were kept indoors for 53 days and then were allowed to graze a contaminated pasture for 50 days for a second natural infection. The third infection was an artificial challenge with 6000 Haemonchus contortus infective larvae. The highest mean fecal egg counts (FEC) values were found in Rambouillet lambs followed in decreasing order by F1, F2 and Florida Native lambs. Throughout the trial, most of the high mean packed cell volumes and plasma protein levels were recorded in the F2 lambs; in contrast, most of the low values were found in the Rambouillet lambs. During the natural infection period, the highest percentages of larvae in the fecal cultures of the lambs were Haemonchus. However, high percentages of Trichostrongylus larvae were found particularly in Florida Native lambs. The mean number of blood eosinophils increased after the artificial challenge, reached a peak 21 days after infection and then declined. The highest and lowest blood eosinophil means were recorded in F2 and Florida Native lambs, respectively. The H. contortus burden was significantly higher in Rambouillet and in F1 lambs than in Florida Native and F2 lambs (p < 0.05), while no significant differences were recorded among eosinophil, mast cell and globule leucocyte counts in the abomasal mucosa (p > 0.05). The highest correlation coefficient recorded at the end of this study was between FEC and worm burden (r = 0.7). These two parameters showed a moderate negative correlation with PCV, plasma protein and mast cell counts in the abomasal mucosa. The results obtained in this study indicate that crossbreeding Florida Native and Rambouillet sheep can be a rapid way to combine and improve the characteristics of these two breeds. The parasitological results were promising. however, more studies will be necessary to verify the impact of crossbreeding in other traits. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: Haemonchus; sheep; nematode; breed resistance; mast cells; globule leucocytes; eosinophils